2023
DOI: 10.1039/d3py00045a
|View full text |Cite
|
Sign up to set email alerts
|

Anl-proline-modified chiral porous hyper-crosslinkedl-phenylalanine dipeptide—increased reaction rate and selectivity in asymmetric catalysis

Abstract: A L-phenylalanine dipeptide (L-Phe-L-Phe-OMe) monomer was cross-linked to form a heterogeneous chiral porous polymer skeleton, HCP(L-Phe-L-Phe-OMe), which was then modified with L-proline (L-Pro) to produce an HCP(L-Pro-L-Phe-L-Phe-OMe) catalyst with a...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Subsequently, the HCP 26 catalyst was further modified with l -proline ( l -Pro) to achieve a specific surface area of 261.68 m 2 g −1 . 103 The catalytic activity of HCP 26 (6 mg) was demonstrated in the successful facilitation of the asymmetric Michael addition reaction and Mannich reaction. In comparison to the unloaded condition, the reaction time for the Michael addition of cyclohexanone with trans -β-nitrostyrene was reduced from 7 days to 4 days, accompanied by an increase in the ee value from 71% to 97%.…”
Section: Insoluble Carrier Supported Catalystmentioning
confidence: 99%
“…Subsequently, the HCP 26 catalyst was further modified with l -proline ( l -Pro) to achieve a specific surface area of 261.68 m 2 g −1 . 103 The catalytic activity of HCP 26 (6 mg) was demonstrated in the successful facilitation of the asymmetric Michael addition reaction and Mannich reaction. In comparison to the unloaded condition, the reaction time for the Michael addition of cyclohexanone with trans -β-nitrostyrene was reduced from 7 days to 4 days, accompanied by an increase in the ee value from 71% to 97%.…”
Section: Insoluble Carrier Supported Catalystmentioning
confidence: 99%
“…In 2023, Wang et al reported a study on the synthesis of chiral porous hyper-crosslinked polymer frameworks using L-phenylalanine dipeptide as a monomer through a simple Friedel–Crafts alkylation reaction. The resulting framework was named HCP(L-Phe-L-Phe-OMe) [ 70 ]. Subsequently, they further modified the framework using L-proline.…”
Section: Structure-oriented Design Of Hyper-crosslinked Polymer Nanom...mentioning
confidence: 99%
“…Reprinted with permission from Ref. [ 70 ], Copyright 2023, Royal Society of Chemistry. ( c ) Pore size distribution of pristine HPOPs and sulfonated HPOPs based on the quenched solid density functional theory (QSDFT) method, with ultramicropore size distribution from CO 2 sorption at 273 K/1.0 bar using the HK mode (inset).…”
Section: Structure-oriented Design Of Hyper-crosslinked Polymer Nanom...mentioning
confidence: 99%